2019
DOI: 10.1093/ageing/afz025
|View full text |Cite
|
Sign up to set email alerts
|

Can comprehensive geriatric assessment be delivered without the need for geriatricians? A formative evaluation in two perioperative surgical settings

Abstract: Introduction the aim of this study was to design an approach to improving care for frail older patients in hospital services where comprehensive geriatric assessment (CGA) was not part of the clinical tradition. Methods the intervention was based on the principles of CGA, using quality improvement methodology to embed care processes. Qualitative methods and coproduction were used to inform development of the intervention, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 17 publications
1
62
0
Order By: Relevance
“…At a healthcare professional level, geriatricians perceived their skill set was unique and valuable for the care of older surgical patients. A recent study showed that implementation of a CGA toolkit to help non-geriatricians deliver CGA for older surgical patients was poorly taken up and implemented, despite buy in from surgeons and anaesthetists at the study hospitals [31]. This echoes the geriatricians' view that they have a specific unique skill set that complements the skills of surgeons and anaesthetists.…”
Section: Discussionmentioning
confidence: 96%
“…At a healthcare professional level, geriatricians perceived their skill set was unique and valuable for the care of older surgical patients. A recent study showed that implementation of a CGA toolkit to help non-geriatricians deliver CGA for older surgical patients was poorly taken up and implemented, despite buy in from surgeons and anaesthetists at the study hospitals [31]. This echoes the geriatricians' view that they have a specific unique skill set that complements the skills of surgeons and anaesthetists.…”
Section: Discussionmentioning
confidence: 96%
“…The place of geriatric teams could be preponderant in order to improve the care of major geriatric syndromes and, more specifically, undernutrition. Previous studies using geriatric outreach teams or aiming to implement protocols that interfere with current practice have had difficulties showing an impact [ 51 , 52 ]. A recent retrospective study on medical and surgical malnourished patients suggested that embedded nutrition-focused quality improvement programs may improve outcomes such as length of stay or 30-day readmissions, especially for surgical patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] Translating this literature into routine clinical care is problematic due to challenges related to an inadequately trained workforce and has been explored in a recent study aiming to deliver Comprehensive Geriatric Assessment, with limited success, by non-geriatricians. 48 Prehabilitation refers to multidimensional interventions aimed at increasing functional reserve prior to surgery, the central tenets being structured exercise programme and nutritional optimisation. Patients with lower preoperative fitness levels have been shown to derive most benefit, 49 but a recent systematic review has concluded that there is a lack of evidence for clinical outcomes in this population, limited by a low number and quality of studies.…”
Section: Discussionmentioning
confidence: 99%